KI HADJAR DEWANTARAâ€™S LEADERSHIP TRILOGY AS FOUND IN TETSUKO KURAYANAGIâ€™S TOTTO-CHAN: THE LITTLE GIRL AT THE WINDOW NOVEL - Apriningtiyas Ana Lestari (Universitas Sarjanawiyata Tamansiswa, 2019)
This research analyzed Ki Hadjar Dewantaraâ€™s Leadership Trilogy as found in Tetsuko Kurayanagiâ€™sâ€œTotto-Chan: The Little Girl at the Windowâ€ novel. The objectives of this research were to 1) describe Ki HadjarDewantaraâ€™s leadership trilogy as found in Totto-Chan: The Little Girl at the Window novel; and 2) find out how the aspects of Ki Hadjar Dewantaraâ€™s Leadership Trilogy found in the novel can be implemented in real life situations. This research applied a qualitative approach. The data collection technique was the document analysis of Oâ€™Leary model, which consisted of three steps, namely plan, interrogate and reflect/refine. The data analysis technique was inductive content analysis, which consisted of four steps, they are: open coding, grouping, creating the categories, and abstraction. The results of this research showed that Ki Hadjar Dewantaraâ€™s leadership trilogy found in Totto-Chan: The Little Girl at the Window novel wereÂ Ing Ngarsa Sung Tuladha, Ing Madya MangunKarsa, and Tut Wuri Handayani. Ki HadjarDewantaraâ€™s leadership trilogy can also be implemented in the real-life situation, especially in education field, for example at Senior High School of Taman Madya Ibu Pawiyatan Yogyakarta.